ALGERIAN RURAL WOMEN’S ACCESS TO THE WORLD OF ENTREPRENEURSHIP TO ATTAIN SUSTAINABLE RURAL DEVELOPMENT - Ketfi Soltana; Nedjla Gherabi (International Journal of Innovative Technologies in Social Science, 2024)
The aim of this study is to highlight the importance of Algerian rural women’s access to the world of entrepreneurship together with its role in attaining sustainable rural development. In fact, the access of rural women to the field of entrepreneurship has shown to be of the essence to attain progress and development in rural areas, as Algeria has paid great attention to rural women through developing several policies for Rural Renewal and Rural Development, in addition to the embodiment of more than a few national programs for their promotion all the way through the policy of encouraging innovation and self-employment pursued by the State, by means of developing mechanisms and adopting national programs with an economic and social dimension aimed at the category of young men, both male and female, based on the provision of facilities and incentives by proffering financial support, guidance, training and accompaniment for creation purpose of mini-projects and start-ups, along with encouraging rural women with a project to access to the entrepreneurship world.